Accelerometer-Based Navigation in Total Knee Arthroplasty for the Management of Extra-Articular Deformity and Retained Femoral Hardware: Analysis of Component Alignment - Cozzi Lepri, Andrea; Innocenti, Matteo; Matassi, Fabrizio; Villano, Marco; Civinini, Roberto; Innocenti, Massimo (Joints, 2019)
Purpose Recent advances in total knee arthroplasty (TKA) include an accelerometer portable system designed to improve component position and alignment. The purpose of this study is to evaluate whether accelerometer navigation system can be a valuable option in complex TKAs for extra-articular deformity of the lower limb or in case of retained femoral hardware.Methods A group of 13 patients underwent TKA with an accelerometer navigation system. Three patients had a tibial extra-articular deformity, six had a femoral extra-articular deformity, and four had an intramedullary nail in the femur. Preoperative and postoperative mechanical axes were measured from full-length lower extremity radiographs to evaluate alignment. The alignment of prosthetic components in the frontal and sagittal planes was determined by postoperative radiographs.Results At 30-days postoperative radiographic check, the hip knee ankle angle was within 2.0° (0 ± 1) of the neutral mechanical axis. The alignment of the tibial component on the frontal plane was 90.0° (range 89–91) and on the sagittal plane 5.0° (range 3–7). The alignment of the femoral component on the frontal plane was 90.0° (range 89–91) and on the sagittal plane 3.0° (range 0–5).Conclusion The alignment of the prosthetic components has been accurate and comparable to other navigation systems in literature without any increase in surgical times. The accelerometer-based navigation system is therefore a useful technique that can be used to optimize TKA alignment in patients with extra-articular deformity or with lower limb hardware, where the intramedullary guides cannot be applied.Level of Evidence This is an observational study without a control group, Level III.
Keywords: total knee arthroplasty; computer navigation; extra-articular deformity; mechanical axis alignment